IDENTIFIKASI WISATA MENGGUNAKAN INDEKS KESESUAIAN WISATA (IKW) DI PANTAI WATUKARUNG KABUPATEN PACITAN JAWA TIMUR - Annasta Aristya Kinanti; Satti Wagistina (GEOGRAPHY : Jurnal Kajian, Penelitian dan Pengembangan Pendidikan, 2025)
Abstrak: Pantai Watukarung dengan keindahan panorama memiliki potensi untuk dikembangkan lebih lanjut menjadi wisata unggulan di Kabupaten Pacitan. Pantai Watukarung kurang dikenal dan diminati oleh masyarakat karena ombak yang cukup besar dan kurangnya informasi bagi pengunjung. Tujuan penelitian ini untuk mengetahui kesesuaian wisata Pantai Watukarung dengan menentukan nilai indeks kesesuaian wisata kategori rekreasi dan berenang. Metode menggunakan deskriptif kuantitatif. Data yang digunakan primer dan sekunder, metode pengumpulan data adalah survei dan pengukuran secara langsung. Pemilihan titik lokasi pengukuran menggunakan metode purpossive sampling, terbagi tiga stasiun. Hasil penilaian Indeks Kesesuaian Wisata dari ketiga stasiun adalah S3 “Sesuai bersyarat” dengan nilai stasiun 1 54.6%, stasiun 2 58.6%, stasiun 3 sebesar 56%. Faktor yang menjadi pembatas adalah kedalaman dan biota berbahaya bulu babi. Kegiatan yang cocok dilakukan bersantai, jalan-jalan, dan bermain di sekitar bibir pantai. Abstract: Watukarung Beach has a beautiful panorama that has the potential to be further developed into a leading tourism destination in Pacitan Regency to improve the economy of the surrounding community and the region. Watukarung Beach is less well known and in demand by the community compared to other beaches in Pacitan Regency due to its large waves and lack of information for visitors. The purpose of the research was to identify the suitability index of Watukarung beach tourism to assess suitable activities carried out by visitors in the area other than surfing and activities that are not allowed in the beach area. Research objectives The assessment was carried out through measurement and observation of several physical and biological parameters. The method used in this research is descriptive quantitative. The data used are primary and secondary data, data collection methods by survey and direct measurement. Selection of measurement location points using purposive sampling method, divided into three stations. The results of the Tourism Suitability Index assessment of the three stations are S3 “Conditionally Suitable” with a value of station 1 of 54.6%, station 2 of 58.6%, station 3 of 54.6%. The limiting factors are large waves, water depth especially in high tide conditions, and dangerous biota namely sea urchins. Activities that are suitable for Watukarung beach are relaxing, sightseeing, playing around the shoreline while remaining vigilant, and swimming.